Digital marketing, customer satisfaction, and customer loyalty in influencing sales at Alfamidi retail - Hidayah, Nurul; Hudayah, Syarifah; Kuleh, J (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2026)
This study examines the influence of digital marketing, customer satisfaction, and customer loyalty on retail sales at Alfamidi. The research aims to determine both the individual and simultaneous effects of these variables on retail performance. A quantitative explanatory approach was employed, with 140 respondents selected using purposive sampling based on their experience with Alfamidi’s digital platforms. Data were collected through online questionnaires, observations, and informal interviews. Partial Least Squares Structural Equation Modeling (PLS-SEM) was applied to analyze the measurement and structural models, including assessments of validity, reliability, coefficient of determination, and path significance. The results indicate that digital marketing, customer satisfaction, and customer loyalty have positive and significant effects on Alfamidi’s retail sales. The R-Square value of 0.724 demonstrates that these three variables collectively explain 71.8% of the variation in retail sales, while the remaining 28.2% is influenced by other factors outside the model. These findings highlight the critical role of integrating effective digital marketing strategies with high-quality customer service to enhance satisfaction and loyalty, thereby driving sales growth and ensuring sustainable business performance in Indonesia’s modern retail sector.